Optical effects of the March 1970 geophysical event at the AFCRL geopole observatory, Thule Air Base, Greenland - Silverman, S. M. (Sam M.); Moore, J. G.; Air Force Cambridge Research Laboratories (U.S.)
The optical observations from Geopole Observatory, Thule A.B., Greenland, during the 6 to 10 March 1970 event are discussed. The spectral data were considered in detail for two periods, on March 6 and March 9, preceding and during the PCA. The ratio of the 5577A (OI) and 6300A (OI) emission intensities for several disturbed periods is found to be consistent with excitation somewhat below the normal F-region heights for production of 6300A (OI). Use of optical and riometer data in conjunction indicates a hardening of the input energy spectrum on the 8th with a strong softening on the 9th, in accord with expectations from the moderate character of the PCA. A comparison of luminosity fluctuations at Qanaq and Geopole lead to movements of excitations with velocities of the order of 250 to 300 m/s. Possible flare effects are noted and discussed. (Author). Presented at IUGG meeting, Moscow, August 1971. Research supported by the Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts. Aeronomy Laboratory Project 7661. AD0744074 (from http://www.dtic.mil). "18 April 1972." Includes bibliographical references (page 13). The optical observations from Geopole Observatory, Thule A.B., Greenland, during the 6 to 10 March 1970 event are discussed. The spectral data were considered in detail for two periods, on March 6 and March 9, preceding and during the PCA. The ratio of the 5577A (OI) and 6300A (OI) emission intensities for several disturbed periods is found to be consistent with excitation somewhat below the normal F-region heights for production of 6300A (OI). Use of optical and riometer data in conjunction indicates a hardening of the input energy spectrum on the 8th with a strong softening on the 9th, in accord with expectations from the moderate character of the PCA. A comparison of luminosity fluctuations at Qanaq and Geopole lead to movements of excitations with velocities of the order of 250 to 300 m/s. Possible flare effects are noted and discussed. (Author). Mode of access: Internet.